Development of Augmented Reality (AR) Learning Media Based on Ethnomathematics for MSME Business: Improving Students' Numeracy and Entrepreneurial Character - Auliya, Ferra; Darmayanti, Rani (Edutechnium Journal of Educational Technology, 2026)
The gap between formal mathematics learning and real business practices results in the low relevance of learning materials in improving numeracy skills and shaping entrepreneurial character in students. Responding to this urgency, this study aims to identify content components and compile initial design specifications (Blueprint) for Ethnomathematics-based Augmented Reality (AR) Learning Media for Doormat Craft MSMEs in Karangrejo, Pasuruan. The method applied is Research and Development (R&D) at the ADDIE (Need Assessment) model analysis stage. Data collection was conducted through interviews with teachers and Systematic Literature Studies (for needs and context analysis), as well as documentation of phenomenological studies (available data) on doormat craft MSMEs (for authentic content analysis). The instruments used include interview guidelines and an Ethnomathematics concept mapping matrix. The main findings indicate a significant need for AR media that can contextualize relevant mathematical concepts—such as calculating raw material ratios and determining price margins—into interactive business scenarios. This in-depth analysis resulted in an AR application Blueprint, which details the content flow and digital interaction model, while ensuring that the Ethnomathematics content explored can be transformed into 3D AR interactive objects. This design specification makes a substantial contribution to this research, by providing a strong empirical foundation for the further development of learning technologies that are effective in improving business numeracy literacy and entrepreneurial behavior in students.